POSITIONAL ISOMERS OF OcTADECENOIC Acm SEPARATED FROM OILS OF THREE CARUM SPECIES OF UMBELLIFERAE FAMILY (Biological Sciences - PJSIR, 2001)
In the family Umbelliferae octadecenoic acid (C18,1 ) is a phylogenetic character having distribution on the different positions of triacylgl ycerol molecules. It has a role as a key i ntermediate in fat metabolism during seed germination which created an interest to i nvestigate futher to find out its positional isomers in the oils of Carum species. Therefore, the octadecenoic acid separated from the seed oil of Canun caplicum, Carum carvi and Carwn roxburghianum of Umbelliferae family was oxidized separated by Von Rudloff 's reagents. The liberated mono and difunctional. fatty acids were separated and identified by the application of thin layer and gas liquid chromatography to determi ne positional isomers. The positional isomers determined among these three species were cis-6-octadecenoic acid, cis-9-octadecenoic acid and  cisl 2octadecenoic acid. The percentage of these isomers varied from 4.5 to 46.0%